The Influence of Physical Activity and Carbohydrate Management on Glycemic Control in Type 1 Diabetes: Exploring the Potential of Artificial Intelligence in Diabetes Care - Dziekoński, Kamil; Popiel, Michal; Wieczorek, Iga; Cybulski, Paweł; Smala, Kamila; Ostojewska, Justyna; Bień, Katarzyna; Szafranek, Adam; Wacławek, Wiktoria; Kwiecień, Iga; Bartoszewska, Karolina (Quality in Sport, 2025)
Purpose: Managing Type 1 Diabetes Mellitus (T1DM) involves balancing mental health, diet, and physical activity (PA). For T1DM patients, maintaining stable glucose levels is difficult due to the risk of both low blood sugar after meals (postprandial hypoglycemia) and complications from high blood sugar (hyperglycemia). This study explores how PA influences glucose regulation and examines carbohydrate intake strategies, control methods, and the potential role of artificial intelligence (AI) in diabetes management. Design/methodology/approach: A systematic review of studies on exercise, diet, and glycemic control in T1DM patients was conducted. Data from meta-analyses, randomized trials, and observational studies were sourced from PubMed, Google Scholar, and ResearchGate. Findings: Regular PA improves glycemic control, lowering glycated hemoglobin (HbA1c), insulin needs, and body mass index (BMI). Structured high-intensity exercise programs lasting over 24 weeks are particularly effective for glycemic control. However, fear of hypoglycemia and work schedules can be barriers. Aerobic exercise reduces visceral fat, while anaerobic exercise enhances glucose uptake and insulin sensitivity.